The Zener-Emitter: A novel superluminescent Ge optical waveguide-amplifier with 4.7 dB gain at 92 mA based on free-carrier modulation by direct Zener tunneling monolithically integrated on Si - Koerner, R.; Schwaiz, D.; Fischer, I. A.; Augel, L.; Bechler, S.; Haenel, L.; Kern, M.; Oehme, M.; Rolseth, E.; Schwartz, B.; Weisshaupt, D.; Zhang, W.; et al. (Technical Digest - International Electron Devices Meeting, IEDM, 2017)
We report on the first experimental demonstration of a monolithic integrated Group-IV Ge semiconductor optical amplifier (SOA) - the Ge Zener-Emitter (ZE). The ZE is a device featuring light amplification up to 4.7 dB (92 mA) at center wavelength of 1700 nm and gain-bandwidth of 98 nm on Si (100). Our novel direct Zener band-to-band tunneling (BTBT) injection method enables low-voltage electron emission beyond the Boltzmann-limit (38 mV/dec at 1.55 K, 88 mV/dec at 300 K), achieving population-inversion at 0.45 V (41 mA). The ZE possesses a Si-Ge-Si hetero-structure with excellent CMOS integration compatibility by planar device design (550 nm) and an ultra-thin (100 nm) Ge virtual substrate (VS) on Si (100). Moreover, the ZE shows superior light emission properties with pulsed lasing at 1667 nm and superluminescent LED characteristic (150 cm-1 max. gain at 270 K, 100 cm-1 max. gain at 300 k). The developed ZE device presents a promising feature to monolithic Si-photonics filling the gap for energy-efficient light emission and amplification in a small footprint (1 mm) integrated waveguide-amplifier.
CRIS-Team Scopus Importer:2021-06-29